From a Home-Area-Network to a Secure Internet of Things Application (2019)
In this paper, we present a secure system to control devices at home through the web, which we implement based on the Do It Yourself (DIY) culture. We use a model based on the Goal Question Metric approach to evaluate the quality of our system. Given that we are now in the era of the Internet of Things (IoT), security must be at the same level or even in a higher priority than other aspects such as speed, size, and power consumption. The objective of this work is to verify that acceptable levels of confidentiality, integrity, availability, access control, authentication and non-repudiation can be guaranteed in open platforms such as Arduino, Galileo, Energia, Tiva C, among others. Taking into account these platforms, we developed a system with access control that implements motion detection, light control, and generates a power consumption record. The results show a comparison between our security implementation and other authors’ implementation. © 2019, Springer Nature Switzerland AG.